1996
DOI: 10.1038/380215a0
|View full text |Cite
|
Sign up to set email alerts
|

State-dependent life histories

Abstract: Life-history theory is concerned with strategic decisions over an organism's lifetime. Evidence is accumulating about the way in which these decisions depend on the organism's physiological state and other components such as external circumstances. Phenotypic plasticity may be interpreted as an organism's response to its state. The quality of offspring may depend on the state and behaviour of the mother. Recent theoretical advances allow these and other state-dependent effects to be modelled within the same fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

22
557
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 764 publications
(579 citation statements)
references
References 63 publications
22
557
0
Order By: Relevance
“…Given the importance of individual variation in optimizing life histories (McNamara and Houston, 1996;Piersma and Drent, 2003), our results are important in demonstrating that individual variation in hormone levels is correlated with parental effort by adult mourning doves. We found that individual variation in both BL CORT and BL PRL levels was positively correlated to parental effort early in the nestling period.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Given the importance of individual variation in optimizing life histories (McNamara and Houston, 1996;Piersma and Drent, 2003), our results are important in demonstrating that individual variation in hormone levels is correlated with parental effort by adult mourning doves. We found that individual variation in both BL CORT and BL PRL levels was positively correlated to parental effort early in the nestling period.…”
Section: Discussionmentioning
confidence: 86%
“…During reproduction, individuals must balance investment in current and future reproduction (Williams, 1966) and are likely to vary their reproductive effort in response to their current state, environmental conditions, and future opportunities (McNamara and Houston, 1996). Endocrine systems have the potential to play an important role in orchestrating decisions to optimize life-history decisions by assimilating input regarding current conditions and adjusting physiology and behavior to optimize investment (Finch and Rose, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, “chronologically young” individuals could be considered “biologically old” and also senesce. Differences in state arise as a result of different life‐history strategies and environmental conditions, generating differences in damage accumulation rates between individuals (McNamara & Houston, 1996; McNamara et al., 2009), and thus potential differences in age at onset and rates of senescence. For example, if reproduction leads to increased damage accumulation, fast reproducing individuals effectively bring forward their own death (McNamara et al., 2009).…”
Section: Introductionmentioning
confidence: 99%
“…It is well established that the probability to reproduce and breeding success in females is not constant across ontogeny (McNamara & Houston, 1996). In several species, including horses, the relationship between the probability to reproduce or breeding success and female age has a typical bell shape, with prime‐aged females having the highest probabilities (Beauplet, Barbraud, Dabin, Kussener, & Guinet, 2006; Garrott et al., 1991; Rauset et al., 2015; Rughetti, Dematteis, Meneguz, & Festa‐Bianchet, 2015; Tettamanti et al., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Based on previous research on other capital breeders, we predicted that costs of reproduction would be greater in poorer quality (Gomendio, Clutton‐Brock, Albon, Guinness, & Simpson, 1990; Hamel, Cote et al., 2009, 2010; Robert et al., 2012) and senescent (Clutton‐Brock, 1984; Hamel, Cote et al., 2010; McNamara & Houston, 1996) females (P1 and P2). We also expected environmental and social factors to modulate the cost of reproduction (Hamel, Cote et al., 2010; Nicolaus et al., 2012; Robert et al., 2012); more specifically, we predicted that the costs of reproduction would increase with winter severity (P3), local conspecific density (P4), and band size (P5).…”
Section: Introductionmentioning
confidence: 99%